Evaluating the impacts of agricultural development and climate change on the water-energy nexus in Santa Elena (Ecuador) - Chengot, Rishma; Zylberman, Raphael; Momblanch, Andrea; Salazar, Oswaldo Viteri; Hess, Tim M.; Knox, Jerry W.; Rey, Dolores (Elsevier, 2024)
A combination of a changing global climate coupled with rapid socio-economic development is putting unprecedented pressure on water, energy, and food resources. Addressing these issues within a nexus approach can help to identify appropriate management practices and strategic policies to ensure natural resources are used more sustainably thus avoiding exacerbating issues of water scarcity and food insecurity. In this study, we used an integrated water resource planning and irrigation model (WEAP) to assess emerging water-energy nexus issues on the Santa Elena peninsula in Ecuador. Simulated water demands showed that current water resources availability is insufficient to meet full irrigation requirements, especially during the dry season. Annual average energy demand for water conveyance in the SEP was significantly higher than for irrigation with 94.5 GWh and 13.5 GWh being used, respectively. Future challenges associated with changes in agricultural irrigation and urban demands within the SEP were evaluated using scenario analysis. This included considering various scenarios such as agricultural expansion, climate change, population growth, and a shift to export-oriented agriculture. The study underscores the significance of nexus thinking in guiding policy and decision-making in Santa Elena, although the limited data prevents its use in an operational framework. The benefits of adopting an integrated modelling approach to analyse water and energy nexus trade-offs are also discussed.
Keywords: Crop irrigation; Water resources; Scenario; WEAP model